Building Fiscal Awareness among Thai High School Students: A Participatory Action Research Experience - Mediaty, Mediaty; Mas’ud, Anis Anshari; Idrawahyuni, Idrawahyuni; Rayyani, Wa Ode; Nurhalija, Nurhalija; Nurwazaila, Nurwazaila; Yusuf , Yusfi Tsabita Nanda; Farman, Safril; Lestari, Nurma (International Journal of Community Service (IJCS), 2025)
This study addresses the limited fiscal awareness among high school students and explores how a participatory approach can foster a better understanding of public budgeting concepts. A one-day community service program was conducted on May 17, 2025, at Sangkhom Islam Wittaya School, Hatyai, Thailand, involving 27 students and several teachers. The program was facilitated by four lecturers and four students from three universities in South Sulawesi, Indonesia: Hasanuddin University, West Sulawesi University, and Muhammadiyah University of Makassar. Using a modified Participatory Action Research (PAR) approach as the educational method, the activity was structured into planning, action, and reflection stages, incorporating interactive workshops, group discussions, and simulated budget allocation exercises. Data were collected through facilitator observations, student responses, and feedback. Findings indicate that students demonstrated an increased understanding of how public resources are managed and the importance of fiscal transparency. This article concludes that experiential and collaborative methods such as PAR are effective in fostering fiscal awareness among youth.